Tadpole Responses to Environments With Limited Visibility: What We (Don’t) Know and Perspectives for a Sharper Future - Fouilloux, Chloe A.; Yovanovich, Carola A. M.; Rojas, Bibiana (Frontiers in Ecology and Evolution, 2022)
Amphibian larvae typically inhabit relatively shallow freshwater environments, and within these boundaries there is considerable diversity in the structure of the habitats exploited by different species. This diversity in habitat structure is usually taken into account in relation to aspects such as locomotion and feeding, and plays a fundamental role in the classification of tadpoles into ecomorphological guilds. However, its impact in shaping the sensory worlds of different species is rarely addressed, including the optical qualities of each of these types of water bodies and the challenges and limitations that they impose on the repertoire of visual abilities available for a typical vertebrate eye. In this Perspective article, we identify gaps in knowledge on (1) the role of turbidity and light-limited environments in shaping the larval visual system; and (2) the possible behavioural and phenotypic responses of larvae to such environments. We also identify relevant unaddressed study systems paying special attention to phytotelmata, whose small size allows for extensive quantification and manipulation providing a rich and relatively unexplored research model. Furthermore, we generate hypotheses ranging from proximate shifts (i.e., red-shifted spectral sensitivity peaks driven by deviations in chromophore ratios) to ultimate changes in tadpole behaviour and phenotype, such as reduced foraging efficiency and the loss of antipredator signaling. Overall, amphibians provide an exciting opportunity to understand adaptations to visually-limited environments, and this framework will provide novel experimental considerations and interpretations to kickstart future research based on understanding the evolution and diversity of strategies used to cope with limited visibility.